Neoadjuvant Immunotherapy of Oral Squamous Cell Carcinoma: Case Report and Assessment of Histological Response - Olmos, Manuel; Glajzer, Jacek; Büntemeyer, Tjark-Ole; Frohwitter, Gesche; Ries, Jutta; Eckstein, Markus; Hecht, Markus; Lutz, Rainer; Kesting, Marco Rainer; Weber, Manuel (Frontiers in Oncology, 2021)
Background: The treatment of oral cancer remains challenging due to its infiltrative nature and a high tendency for tumour relapse leading to an overall poor prognosis. In the case of early recurrence, the patient’s prognosis deteriorates dramatically, with survival rate dropping to below 30%. Minimal improvements in survival trends in recurrent and advanced stage tumours have been reported in recent decades. Neoadjuvant immunotherapy may represent a new therapeutic approach changing the standard of care in advanced oral cancer therapy. Case Presentation: We describe the case of a woman in her late 30’s who presented in mid-2019 with oral squamous cell carcinoma (OSCC) localized to the floor of the mouth. After initial R0 resection, selective neck dissection, and adjuvant brachytherapy, an early recurrence of OSCC located between the hyoid bone and the mandible was diagnosed at the end of 2019. An off-label treatment regimen was performed with neoadjuvant use of Pembrolizumab 19 days prior to salvage surgery. Radiological and histological assessment of T-cell and programmed cell death protein 1 ligand 1 (PD-L1) expression was performed before and after checkpoint inhibitor application. Neoadjuvant immunotherapy resulted in increased T-cell infiltration and PD-L1 expression, as well as a significant tumour necrosis rate. One cycle of Pembrolizumab led to significant regressive tumour changes with increases in immune infiltration, sclerosis, and necrosis of 75% of the tumour mass with only 25% vital tumour cells remaining. By June 2020, the patient remained without recurrence. Conclusions: The case presented outlines the potential effects of neoadjuvant immunotherapy in recurrent or advanced OSCC prior to definitive surgical tumour treatment. The benefit of additional adjuvant treatment after histologic response will be discussed. The case is also analysed considering ongoing clinical trials of neoadjuvant immunotherapy for head and neck malignancies.
CRIS-Team Scopus Importer:2021-08-13
Keywords: case report; immune checkpoint inhibitors; immunotherapy; neoadjuvant; oral cancer; OSCC; PD-1 - PD-L1 axis; pembrolizumab